Energy Security, Economics and Environment in the Eurasian Economic Union: Current and Future Scenarios - Saiymova, Meiramkul; Shakharova, Aliya; Rakaeva, Aliya; Serikova, Madina; Tasmaganbetov, Aslan; Tyurina, Yuliya; Bimagambetova, Zhibek (International Journal of Energy Economics and Policy, 2020)
The Eurasian Economic Union (EAEU) countries have actively taken a direction to promote political initiatives to strengthen energy security. Major policy initiatives are programmes to increase domestic renewable energy production, improve energy efficiency and reduce CO2 emissions from fossil fuel combustion. This paper aims to show how energy security indicators namely primary energy intensity of GDP (EI), primary energy dependence (PE), net import dependence (ID), supplier dependency (SD) vary in a range of energy security policies - Renewable Energy Development (REN), Energy Efficiency Reduction (EFF), and Greenhouse Gas Reduction (GHG). Furthermore, factors preventing the development of non-traditional and renewable sources of energy in countries of Eurasian Economic Union are considered. Mechanisms of solving existing contradictions are proposed. Particular attention is paid to the need to include environmental costs and pollution losses in economic analysis, which will improve the competitiveness of alternative energy sources. The necessity of accelerated development of alternative energy to increase energy supply, energy saving, energy and environmental security is shown. Keywords: renewable energy, energy security, sustainable development JEL Classifications: 0130, Q400, Q430 DOI: https://doi.org/10.32479/ijeep.9127